2014
DOI: 10.3892/etm.2014.1863
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of carvedilol: inhibition of apoptosis in H9c2 cardiomyocytes via the TLR4/NF-κB pathway following ischemia/reperfusion injury

Abstract: Carvedilol is a non-selective β-blocker used in the treatment of cardiovascular disease, including myocardial ischemia. The aim of the present study was to investigate the molecular mechanisms underlying the effects of carvedilol on simulated ischemia/reperfusion (SI/R)-induced cardiomyocyte apoptosis in vitro. H9c2 cardiomyocytes were incubated with either a vehicle or an ischemic buffer during hypoxia followed by reoxygenation with or without carvedilol. In two additional groups, toll-like receptor 4 (TLR4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
(23 reference statements)
1
20
0
Order By: Relevance
“…Accumulating evidence indicates that apoptosis-and autophagy-associated myocyte death play key roles in the induction of MIRI (9,19,27). Our present study demonstrated that the overexpression of RP105 via a recombinant adenoviral vector is a promising cardioprotective strategy to induce anti-apoptotic and anti-autophagic effects in MIRI in vivo.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Accumulating evidence indicates that apoptosis-and autophagy-associated myocyte death play key roles in the induction of MIRI (9,19,27). Our present study demonstrated that the overexpression of RP105 via a recombinant adenoviral vector is a promising cardioprotective strategy to induce anti-apoptotic and anti-autophagic effects in MIRI in vivo.…”
Section: Discussionsupporting
confidence: 62%
“…Herein, our data showed, for the first time to the best of our knowledge, that the TLR4, p-NF-κB/p65, and IL-6/ TNF-α signaling pathways were upregulated in MIRI, and therfore promoted apoptosis. These results, taken together with other findings (19,29), regarding the TLR4/NF-κB-IL-6 (TNF-α)-mediated apoptotic mechanism broaden our understanding of the multiple biological functions of TLR4, beyond being a canonical inflammatory sensor in MIRI.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A reduction in expression levels of TLR4 and NF-κB is an efficient way for carvedilol to inhibit ischemia/ reperfusion-induced apoptosis [36]. Taking all of our findings and previous findings together, we speculate that TLR4 activates the transcription of inflammation cytokines as well as proapoptotic signaling that results in cell death.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 50%